Granulocyte macrophage-colony stimulating factor (GM-CSF) induced severe atypical rash in a patient of non-hodgkin's lymphoma - Gautam Kumar Singh; Anuj Bhatnagar; Debdeep Mitra; Pooja Sharma; Abhay Singh; Barnali Mitra (Wolters Kluwer Medknow Publications, 2022)
Granulocyte-macrophage colony-stimulating factor (GM-CSF) infusion has been reported with the development of transient maculopapular rash with spontaneous resolution. A 54-year-old Indian female developed intense erythematous generalised rash involving the face, trunk, extremities, palms and soles following GM-CSF infusion. Focal exudation and purpura were seen. Infusion was stopped and she was managed with a short course of systemic steroids. As yet, the development of such an atypical, severe rash following this cytokine infusion has not been reported in the literature.